ANALISIS PEMBELAJARAN PENJUMLAHAN BERSUSUN UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS 3 DI SD NEGERI 5 DOOM: ANALYSIS OF LEARNING ON COMPOSITE ADDITION TO IMPROVE STUDENTS' UNDERSTANDING OF GRADE 3 AT STATE ELEMENTARY SCHOOL 5 DOOM - Payapo, Fatmawati; Anwar, Zakiyah; Sijabat, Jenro Pandu (KAMBIK: Journal of Mathematics Education, 2024)
This study aims to analyze the results of mathematics learning on the material of stacked addition in grade 3 of SD Negeri 5 Doom. With a quantitative descriptive approach, data were collected through a post-test involving 19 students as samples. The results showed that only 47% of students achieved scores above the Minimum Completion Criteria (KKM) of 75, while the other 53% were still below the KKM. Factors such as lack of interest in learning, limited learning tools, and minimal family assistance are the main causes of student difficulties. Analysis of the answers shows that low-ability students often make mistakes in understanding questions (Reading comprehension), students with moderate abilities tend to make mistakes in writing answers (Encoding Error), while high-ability students show good mastery. This study recommends the use of interactive learning methods, additional exercises, and intensive assistance from teachers and parents to improve student understanding evenly.